Life of patients 10 years after a successful pediatric intestinal transplantation in Europe. Issue 6 (25th January 2018) - Norsa, Lorenzo; Gupte, Girish; Ramos Boluda, Esther; Joly, Francisca; Corcos, Olivier; Pirenne, Jacques; Herlenius, Gustaf; Lacaille, Florence
Abstract : A multicenter Europe‐wide single‐point study in intestinal transplantation (ITx) centers was conducted to identify and describe patients surviving for more than 10 years after ITx in childhood. The health and nutritional status, care requirements and psychosocial status were recorded. Among 120 transplanted before 2005, 38 patients with a functioning graft were included. Thirty (79%) had an exclusive oral diet, seven (18%) complimentary enteral nutrition for eating disorders, and one a combination of parenteral and enteral nutrition. They received a median of five drugs daily and five had a stoma. We did not observe any catch‐up growth during the 10 years of follow‐up. In the previous five years, 22 patients needed unplanned hospitalization with a median in‐patient stay of six days. Eleven needed ongoing psychiatric follow‐ups, and nine needed other specialist follow‐ups. An increasing independency from parents was seen after the age of 18, with three having a stable employment and 31 pursuing education. Despite a good graft function, growth may not catch up. The burden of medical care remains high in the long term. This has to be closely followed in a multidisciplinary setting to improve long‐term quality of life in these patients. Abstract : This European survey of pediatric intestinal transplantation demonstrates that long‐term survival, even if scarce, is possible and requires prolonged multidisciplinary follow‐up.